An Investigation on the Editorial Staff of Christian Weekly Tien Feng (1945–1949) - LI, Wenli (Journal of Research for Christianity in China (JRCC), 2024)
Tien Feng, which was founded in 1945, has a special and important position in the history of Chinese Christian press. It is an indispensable reference for the study of Chinese Christian history from 1945 to the present. Because of the journal’s own reasons, it is unclear who the early editors were and when their tenure was. In this research, starting from verifying and sorting out the editorial staff of Tien Feng, relevant historical documents are collected. On the basis of this, the process of the journal from relatively simple in the early days to increasingly mature and complete is investigated.